Changing Patterns Of Industrial Relationships In The Responsive And Justice Era Of The Industrial Revolution 4.0 - Jumiati, Agatha; Slamet Pradoto, Waluyo (CV. Inara, 2022)
The Industrial Revolution 4.0 in the industrial sector has brought changes, one of which is a change concerning the pattern of industrial relations between workers and employers. The pattern of industrial relations before the Industrial Revolution 4.0 was a pattern of relationships based on work agreements. While the pattern of industrial relations after the Industrial Revolution 4.0 underwent a change where the pattern of industrial relations created was based on partnership relations. The pattern of industrial relations based on partnership relations creates an equal or equal relationship and not a multilevel relationship. From the perspective of responsive law, it views the law as an inseparable part of the social world that surrounds it so that the law is not only truly functional and useful in serving the community but is also able to respond to the aspirations and social needs to be served. In a responsive legal order, law is a social institution. Therefore, law is not only seen as a mere regulatory system, but also how the law carries out social functions in and for society. From the perspective of the Theory of Justice presented by John Rawls, it can be concluded that the changing pattern of industrial relations in the Industrial Revolution 4.0 era is in line with the basic principles of justice, namely the principle of freedom and the principle of distribution of income or wealth. This can be reflected in the freedom to draw up work agreements to be made between workers and employers. Besides, the opportunity or opportunity for workers to be able to work in more than one company will encourage unequal distribution of income or wealth. For Rawls' theory, everyone has the same right to be rich, not the right to have the same wealth.